1992
DOI: 10.1080/18811248.1992.9731607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dry Density on Diffusion of Some Radionuclides in Compacted Sodium Bentonite

Abstract: Dry density of bentonite affected the diffusivity for the radionuclide and the apparent diffusion coefficient decreased with increasing dry density of bentonite.Small effect of dry density of bentonite on retardation factor which was derived from the apparent diffusion coefficient was indicated for 137 Distribution coefficient derived from the apparent diffusion coefficient showed a tendency of decreasing with increasing dry density of bentonite except for 237 Np and 241 Am whose coefficients were unchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…To determine the ratio Γ of Re (VII) in experiment, we need to predict the D e of HTO in the same clays. At the compacted dry density of 1,600 kg/m 3 , D e of HTO was reported around 1.1 × 10 −10 m 2 /s in GMZ bentonite (Wu, Dai, et al, 2012) and around 0.95 × 10 −10 m 2 /s in Na‐bentonite (Sato et al, 1992). It was 1.0 × 10 −10 to 1.8 × 10 −10 m 2 /s in compacted clay at dry density of 1,550 kg/m 3 (Tachi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the ratio Γ of Re (VII) in experiment, we need to predict the D e of HTO in the same clays. At the compacted dry density of 1,600 kg/m 3 , D e of HTO was reported around 1.1 × 10 −10 m 2 /s in GMZ bentonite (Wu, Dai, et al, 2012) and around 0.95 × 10 −10 m 2 /s in Na‐bentonite (Sato et al, 1992). It was 1.0 × 10 −10 to 1.8 × 10 −10 m 2 /s in compacted clay at dry density of 1,550 kg/m 3 (Tachi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Since the pore size is very small, many studies have shown that the diffusion process dominates the transportation of radionuclides in bentonite buffer (Idiart & Pękala, 2016; Tournassat & Appelo, 2011; Van Loon et al, 2007). Radionuclides diffusion is influenced by many factors, such as dry densities of bentonite (Sato et al, 1992; Wu et al, 2018), salinities and compositions of pore solution (Glaus et al, 2020; Tachi & Yotsuji, 2014; Wigger & Van Loon, 2018), and sizes and shapes of clay particles (Tertre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In all of the approaches to characterizing the porosity of bentonite, the most important factor controlling the material microstructure is density (Sato et al , 1992; Marcial et al , 2006; Muurinen et al , 2013). It is expected that the degree of compaction affects the pore structure, but the following results show the finer influence of purification and chemical conditions observed with various methods.…”
Section: Resultsmentioning
confidence: 99%
“…[67] This affirmation is reinforced by measurements of effective iodide diffusion coefficients. In high-density materials, chloride and iodide have very similar behavior with respect to diffusion [Kozaki et al, 1998;Sato et al, 1992]. Iodide D e measurements performed using diffusion-permeation experiments [Pocachard et al, 1998] range between 1.4 and 2.4 Â 10 À13 m 2 s À1 , and reflect the extremely slow diffusion properties for chemical species in Tournemire argillites and marls.…”
Section: Reliability Of Method: Comparison With Results On Other Claymentioning
confidence: 99%